Memaknai Pengelolaan Keuangan Kelompok Tani Borneo Citra Lestari - Hidayati; Eriawaty Eriawaty; Revnussa Octobery; Rahman Rahman; Kharisma Nugraha Putra (FKIP Universitas Palangka Raya, 2023)
This research aims to understand and interpret the financial management of farming business groups. The research was conducted at one of the farming business groups in Central Kalimantan Province. This research is a qualitative descriptive research. The results of the research show that the Citra Borneo Lestari Farmers Group has not carried out proper financial planning or recording. Income from agricultural products relies on the farmer's ability to save when the farming cycle is good and then spend it when the farming cycle declines. Because farmers do not plan, financial goals often cannot be achieved. The recommendation from the results of this research is that the Citra Borneo Lestari farmer group should increase their knowledge and financial management of farming through training and financial guidance so that they are trained and skilled in financial management.